Engineering Systems, Dynamics, Modelling, Simulation, and Design - Tabatabaian, Mehrzad (Open textbook library., 2024)
This open educational resource presents effective system modelling methods, including Lagrangian and bond graph, and the application of a relevant engineering software tool, 20-sim. The content is designed for engineering students and professionals in the field to support their understanding and application of these methods for modelling, simulation, and design of engineering systems. The text also includes videos showing selected worked-out examples.